(untitled) (Scientific journal of the Fergana State University, 2023)
The article reveals the world of symbolic images based on Ulugbek Khamdam’s story “Safar” and its place in the essense of the story, its place in the art of the idea of the work. The ratio of the writer’s system of symbolic images, the idea of narrative style symbolism in the essence of the work with the spirit of the time is revealed. The types of symbolic images used in the author’s prose works are proven based on the texts of the works. Narrating from the third-person language in the writer’s stories allows the work to involve various methods of psychological representation. Internal monologues, open confessions, dreams, and hallucinations are easily mixed into such stories. After all, the story from the third-person language can have a free relationship with time, time can be stopped for a long time during the momentary analysis of the human psyche, or brief information can be given about the events of the work. An example of this is the relationship between plot branches. This allows the creator to acquire the artistry of the psychological image in the general storytelling style, to shift the reader’s attention from the development of events to emotions. With the help of symbolic images and artistic images, a person feels the psyche of other people with the power of a divine miracle, imagines them as living people, just like in real life. In the form of symbolic images, a new, mysterious, magical, unique divine world of images is revealed every time.